Development of multi-gap resistive plate chambers with low-resistive silicate glass electrodes for operation at high particle fluxes and large transported charges - Wang, Jingbo; Wang, Yi; Zhu, Xianglei; Ding, Weicheng; Li, Yuanjing; Cheng, Jianping; Herrmann, Norbert; Deppner, Ingo Martin; Zhang, Yapeng; Loizeau, Pierre-Alain; Senger, P.; Gonzalez-Diaz, D. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
Using electrodes made of semi-conductive glass is an innovative way of improving the rate capability of resistive plate chambers. To address this issue, we developed 6- and 10-gap counters with low-resistive silicate glass electrodes (bulk resistivity ∼1010Ωcm) suited for time-of-flight (TOF) applications at high rates and high transported charges. Measurements were performed at GSI-Darmstadt under uniform an irradiation by secondary particles stemming from proton reactions at 2.5GeV/A. For the 10-gap MRPC, time resolutions below 90ps and efficiencies larger than 90% were obtained at counting rates up to 25kHz/cm2. When the particle flux increases every 5kHz/cm2, the efficiency decreases by 1% and the time resolution deteriorates by 4ps. A tolerable decrease of the material conductivity was also observed for a total transported charge of 1C/cm2.
In der Verfasserangabe wurde der Name des Autors "Herrmann" falsch geschrieben, es muss heißen: "Norbert Herrmann"
Gesehen am 10.10.2023